Evaluation of transdermal gels in the delivery of hormone replacement therapy (Research, Society and Development, 2021)
Hormone replacement therapy (HRT) has been increasingly used in people who have low hormone levels. In menopausal women, the therapy is well known for the association of estrogens and progestin’s, while in hypogonadal men, the therapy is carried out through testosterone replacement. For a safer administration of these hormones, the transdermal route has been used to promote a modified release of the active, in addition to avoiding the first-pass effect of the drugs. However, there is much debate about the effectiveness of transdermal formulations in achieving physiological hormonal serum levels compatible with therapeutic levels. The study aimed to conduct a literature review on the safety and efficacy of transdermal gels in the delivery of sex steroid hormones: estrogen, progesterone, and testosterone, used in HRT. The following platforms were used: Academic Google, PubMed, and Capes Periodicals. The use of the transdermal route for the formulation of gels in the delivery of testosterone achieved efficacy, but safety was not guaranteed by the instability of serum hormone levels in the systemic circulation, while progesterone was not effective, as it was not able to reach ideal physiological levels, while estrogen was well tolerable and effective, being the best alternative compared to oral formulations in efficacy and safer for the patient undergoing HRT.